Platinum Single Atoms Strongly Promote Superoxide Formation in Titania-Based Photocatalysis – Platinum Nanoparticles Don't - Wang, Yue; Wu, Siming; Zoppellaro, Giorgio; Baďura, Zdeněk; Schmuki, Patrik (Small, 2025)
The selective reduction of molecular oxygen to superoxide is one of the key reactions in electrochemistry and photocatalysis. Here the effect of Pt co-catalysts, dispersed on titania, either as single atoms or as nanoparticles, on the photocatalytic superoxide (•O2−) formation in O2 containing solutions is investigated. The •O2− formation is traced by nitroblue tetrazolium (NBT) assays and in detail by EPR measurements using TEMPO as •O2− radical scavenger. The results show that the photocatalytic formation rate of •O2− on titania can strongly be enhanced by using Pt single atoms as a co-catalyst, whereas Pt nanoparticles hardly exhibit any accelerating effect. This finding is of considerable significance regarding photocatalytic degradation and photocatalytic oxidative synthesis processes.
CRIS-Team Scopus Importer:2025-03-14
Keywords: degradation; photocatalysis; Pt single atoms; superoxide; titanium dioxide